Risk factors for adverse reactions caused by abemaciclib in breast cancer therapy - Quan, Xianghua; Sun, CaiHong; Han, Bing; Zhang, ChuanZhou; Cang, HuaiQin; Xing, Xiaomin; Guo, Qie (Frontiers in Oncology, 2025)
IntroductionIn recent years, a range of cyclin-dependent kinase 4/6 (CDK4/6) inhibitors have been identified as significantly improving the survival of patients with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2-) breast cancer (BC). As the use of CDK4/6 inhibitors continues to increase, safety concerns have garnered increasing attention. Herein, this study analyzed adverse reactions in breast cancer patients receiving a CDK4/6 inhibitor abemaciclib, with a focus on identifying risk factors for diarrhea and neutropenia through regression analysis.MethodsIn this study, a total of 216 BC patients receiving abemaciclib were enrolled. Follow-up observations towards the baseline and clinical characteristics in these patients were exhibited. The evaluation of adverse effects (AEs) in these patients was performed based on the clinical practice of abemaciclib whole-course management and the consensus on the management. Subsequently, we focused on the two most common adverse reactions during the use of abemaciclib, namely diarrhea and neutropenia. Furthermore, analysis of factors influencing incidence of diarrhea and neutropenia was executed using the univariate analysis and multivariate logistic regression analysis. ResultsThe safety profile of abemaciclib was manageable, and the drug was well tolerated by patients. The incidence of AEs was greater in the gastrointestinal system, blood and lymphatic system, liver system, renal system, muscular and skeletal systems, and skin and subcutaneous tissue systems. Age stratification and gastrointestinal diseases were independent risk factors for grade 2-3 diarrhea. Alternatively, the Eastern Cooperative Oncology Group (ECOG) score was a factor associated with the risk for grade 3-4 neutropenia. Baseline BMI classification, baseline white blood cell (WBC) count and baseline albumin (ALB) stratification were factors associated with protection against grade 3-4 neutropenia.DiscussionThis study retrospectively collected, processed, analyzed, and evaluated the safety profile of abemaciclib. Additionally, potential influencing factors associated with common adverse reactions including diarrhea and neutropenia were explored to provide a foundation for its rational clinical application.